Liberalisation of services in malaysia: is malaysian professionals ready to compete? - Alavi, Rokiah (The Centre for WTO Studies, 2015)
In 2012, the Malaysian Government announced liberalisation of 27 services sectors, including selected professional services. This announcement came as a surprise to the industry players because they have been protected all these while and that it came unexpectedly too soon. This paper intends to investigate the level of awareness and the readiness of professional service providers in Malaysia in facing greater competition as a result of liberalisation of the sector. A case study was done on consultant engineers in Malaysia using survey and questionnaire research methods.